2016
DOI: 10.18805/ijar.11420
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary supplementation of herbal growth promoteron performance of commercial broiler chicken

Abstract: The present study was conducted to evaluate the effect of a Commercial Herbal Growth Promoter (CHGP) with a combination of selective nine numbers of herbs on the performance of broiler chicken. A total of 120 day-old commercial broiler chicks having similar body weight from a single hatch were procured and chicks were randomly distributed into four groups viz, T 0 (standard basal diet as control), T 1 (basal diet + 1.0 % CHGP powder), T 2 (basal diet + 2.0 % CHGP powder) and T 3 (basal diet + 3.0 % CHGP powder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 5 publications
3
11
1
Order By: Relevance
“…Body weight obtained from this study is lower than the results of research Mahanta et al (2017), which ranges from 1825.17g to 2059.83 g. This is due to the use of supplementation of herbal growth promoter. The same results are also obtained by Borah et al (2015) and Vidyarthi et al (2010).…”
Section: Feed Conversioncontrasting
confidence: 74%
“…Body weight obtained from this study is lower than the results of research Mahanta et al (2017), which ranges from 1825.17g to 2059.83 g. This is due to the use of supplementation of herbal growth promoter. The same results are also obtained by Borah et al (2015) and Vidyarthi et al (2010).…”
Section: Feed Conversioncontrasting
confidence: 74%
“…Dry matter (DM) and ether extract (EE) digestibility were reported to be higher with dietary supplementation of mushroom in broiler study (Shang et al, 2016). In addition, feed additives originated from plants can stimulate the digestive functions and therefore could be used in poultry rations as feed additives (Mahanta et al, 2017). In contrast with Daneshmand et al (2012) reported that inclusion of oyster mushroom and antibiotic treatments could not affect protein and organic matter retention in broiler.…”
Section: Apparent Nutrient Retentionmentioning
confidence: 99%
“…Thus, the layer farmers fall into huge economic losses. Antibiotic feed additives have long been used as growth promoters in poultry nutrition (Mahanta et al, 2017). The extensive use of antibiotics in poultry industry with the purpose of increasing production performance has led to human health hazards.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent modern poultry farming practices have led to a search for a better production management system. In the past, antibiotics were used to prevent disease and improve the performance of poultry (Okoro et al, 2016;Mahanta et al, 2017). However, the overuse of antibiotics caused concern about increasing bacterial resistance (Alhidary et al, 2016;Khan et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%